Built environment, creativity, social art. The recovery of public space as engine of human development - Onesti, Anna (REGION, 2017)
The paper is a part of a comprehensive research aimed at operationalizing HUL approach and experimenting it in the buffer zone of Pompei, mainly in Torre Annunziata (Italy), and is based on the recognition of art and cultural heritage as tools for "managing the change" of landscape. The proposed thesis is that the recovery of public space, configured by art and culture and shared with local community according to an inclusive approach, contribute to regenerate creativity, reconstructing the relationships between people, communities and landscape. This lays the foundations for a "creative environment" and regenerative, concived as a prerequisite of development. In this process, art is a driver which acts on the creativity of local residents, stimulating their critical thinking, open-mindedness and design capacity, and leading them to accept diversity as an opportunity. Focusing on theories and on the empirical analysis of a best practice, MAAM Museum in Rome, this paper has three main objectives: to produce empirical evidence on the cause/effect relationship between art, heritage and community relationships; to make transferable and replicable in other contexts, such as Torre Annunziata, the process experienced at MAAM; to develop a methodology able to soliciting, integrating and supporting the regeneration of relationships in the town of Torre Annunziata.